Factors Associated with Maternal Morbidity among Black Women in the United States - Ibrahim Sous, Catrine; Moravec, William; DeFranco, Emily; Kelly, Elizabeth A.; Rossi, Robert M. (American Journal of Perinatology, 2024)
Objective Non-Hispanic Black people (NHBP) have a three-fold higher rate of maternal mortality compared to other racial groups. Racial disparities in maternal morbidity are well-described; however, there are substantial differences in cultural, economic, and social determinants of health among racial groups. We thus sought to study the at-risk, non-Hispanic Black population as its own cohort to identify factors most associated with severe maternal morbidity (SMM).Study Design This is a population-based retrospective case–control study of all live births in the United States between 2017 and 2019 using birth records obtained from the National Center for Health Statistics. The primary outcome for this study was to determine demographic, social, medical, and obstetric factors associated with maternal morbidity among NHBP who did and did not experience an SMM event. Multivariable logistic regression was used to estimate the adjusted odds ratio between each individual factor and the outcome of SMM among NHBP.Results Of the 1,624,744 NHBP who delivered between 2017 and 2019, 1.1% experienced an SMM event defined as a composite of blood product transfusion, eclamptic seizure, intensive care unit admission, unplanned hysterectomy, and uterine rupture. The rates of these individual SMM events per 10,000 deliveries were 50, 40, 20, 5, and 4 among NHBP, respectively. Among NHBP, factors associated in multivariable regression analysis with SMM in order of strength of association included cesarean delivery, earlier gestational age at delivery, preeclampsia, induction of labor, chronic hypertension, prior preterm birth, lower educational attainment, multifetal gestation, advanced maternal age, pregestational diabetes, and cigarette smoking. The population attributable fraction for cesarean delivery, preterm birth, and pregnancy-induced hypertensive disease for the outcome of SMM were 0.46, 0.23, and 0.07, respectively.Conclusion The three factors most associated with SMM among NHBP are potentially avoidable or modifiable by aggressive screening, prevention, and treatment of preeclampsia and preterm birth as well as reducing cesarean rates in this population.Key Points
Keywords: severe maternal morbidity; preeclampsia; preterm birth; black pregnancy outcomes